Honor, play, restore: an exploration of a golf landscape designed as a therapeutic environment to honor U.S. combat veterans and service members - Mannix-Slobig, Brendan (Kansas State University, 2014)
Golf landscapes have been cast as selfish land use, only for the recreation of those who are fortunate enough to play (Kiss, 1998). Recently, golf has been used by precedent programs like the Salute Military Golf Association (SMGA) and American Lake Veterans Golf Course (ALVGC) for its perceived therapeutic value, specifically for those who are suffering from post-traumatic stress disorder (PTSD). The following study presents an academic exploration of the potential therapeutic benefits a therapeutic golf landscape can provide U.S. combat veterans and service members suffering from PTSD. Ownership at a golf course in House Springs, Missouri is inspired to renovate their facilities to incorporate a playing experience of honor and healing for combat veterans. The golf course at Deer Creek USA is used as a model landscape for the purpose of this study. An analysis of the existing literature on the subjects of golf course design, therapeutic landscapes and memorial landscapes provided the foundation for the study. Precedent studies were used to extract specific design principles from each subject which was next interpreted and presented into two design frameworks. The design frameworks informed a series of design consideration for both memorial landscapes and therapeutic landscapes. A detailed analysis of the existing conditions at Deer Creek USA revealed that the golf course needed an intensive renovation in order to meet the report’s goals and objectives. The final Renovation Master Plan is one of many potential applications of the design guidelines to illustrate a vision for Deer Creek USA as a therapeutic landscape for U.S. combat veterans and service members. The following report reveals an innovative approach to the renovation of a golf course specifically designed to foster a complementary form of therapy for PTSD. If built, Deer Creek USA would be a place where U.S. combat veterans and service members suffering from PTSD can go to feel honored while benefiting from the potentially therapeutic sport of golf in a landscape optimized for stress reduction.
Keywords: Therapeutic; Landscape; Golf Course; Memorial; Design; Architecture; Landscape Architecture (0390)